Psychosocial work environment and employee wellbeing: Stress and personality effects - Mubeen, Muhammad; Ali, Muhammad Asad; Muhammad Akbar, Waqar; Kumar, Manoj; Mat, Zawiah (Editora Dom Helder, 2025)
The study examines the impact of the psychosocial work environment, measured as a high-order construct, on employee wellbeing, with stress as a mediator and personality as a moderator. The study collects the data from 230 employees across multiple sectors in Pakistan. Using Partial Least Squares Structural Equation Modelling, the results reveal that psychosocial work environment has a positive effect on employee wellbeing both directly and indirectly through the reduction of stress. Additionally, personality significantly moderates stress and well-being relationships, indicating that individual differences influence the extent to which stress impacts wellbeing. These findings are consistent with Job Demands–Resources and Conservation of Resources theories. This study contributes by validating PWE as a multidimensional construct within a single integrated model, offering new insights for enhancing wellbeing in developing country contexts. The findings suggest that organisations should enhance leadership capabilities, manage workloads effectively, and minimize offensive behaviour to foster supportive work environments. Further, improving psychosocial work conditions promotes healthier workplaces, leading to improved mental health and productivity in the broader society. ping country contexts.